Comparative Survey of Holding Positions for Reducing Vaccination Pain in Young Infants - Hui-Chu Yin; Shao-Wen Cheng; Chun-Yuh Yang; Ya-Wen Chiu; Yi-Hao Weng (Pain Research and Management)
Background. Infant holding position may reduce vaccination pain. However, the optimal position for young infants remains controversial. Objectives. To compare the effectiveness of holding infants in the supine position and the effectiveness of holding infants in upright position for relieving acute pain from vaccine injection. Methods. This prospective cohort study enrolled 6–12-week-old healthy infants. We examined infant pain responses by evaluating the following three categories: (1) crying, (2) irritability, and (3) facial expression. Results. In total, 282 infants were enrolled, with 103 and 179 held in the supine and upright positions, respectively. At 30 s after vaccination, the infants in the supine position showed a larger decrease in crying (p<0.001), irritability (p=0.002), and pained facial expression (p=0.001) than did those in the upright position. However, there was no significant difference in pain response between two groups at 180 s after intervention. Conclusion. In 2-month-old infants, the supine position may reduce acute pain more effectively than does the upright position. Our findings provide a clinical strategy for relieving vaccination pain in young infants.